2016
DOI: 10.1007/s00300-016-1982-2
|View full text |Cite
|
Sign up to set email alerts
|

Do benthic meiofaunal and macrofaunal communities respond to seasonality in pelagial processes in an Arctic fjord (Kongsfjorden, Spitsbergen)?

Abstract: This study explores whether the marked seasonality in pelagic productivity and phytodetritus fluxes to the sea bottom in an Arctic fjord is reflected in variability of benthic communities in terms of taxonomic composition and standing stocks. Three stations located along the Kongsfjorden (west Spitsbergen) axis were visited in four seasons (May, August, October and January), and meiofauna and macrofauna was sampled. The elusive seasonal variability in benthic attributes contrasted with the clear seasonal effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 53 publications
3
13
0
Order By: Relevance
“…It is possible that in those regions detectable seasonal variation in size structure of benthic communities can also occur, but further studies are needed to test it. Lack of seasonal patterns in benthic size spectra is consistent with the study of Włodarska-Kowalczuk et al (2016), who did not found a clear response of Kongsfjorden benthic standing stocks or diversity to changes of organic matter supply during four seasons. Their findings and the present study support the hypothesis of the sediment 'food bank' existence in the polar sediments that was first formulated for the West Antarctic Peninsula by Mincks et al (2005).…”
Section: Benthic Response To Seasonal Variability In Kongsfjorden Ecosupporting
confidence: 89%
See 1 more Smart Citation
“…It is possible that in those regions detectable seasonal variation in size structure of benthic communities can also occur, but further studies are needed to test it. Lack of seasonal patterns in benthic size spectra is consistent with the study of Włodarska-Kowalczuk et al (2016), who did not found a clear response of Kongsfjorden benthic standing stocks or diversity to changes of organic matter supply during four seasons. Their findings and the present study support the hypothesis of the sediment 'food bank' existence in the polar sediments that was first formulated for the West Antarctic Peninsula by Mincks et al (2005).…”
Section: Benthic Response To Seasonal Variability In Kongsfjorden Ecosupporting
confidence: 89%
“…For meiofaunal nematodes and Prionospio cirrifera, the individual biomass was lower at stations KB1 and KB2, but higher at KB3. Włodarska-Kowalczuk et al (2016) showed no difference in mean individual biomass of Nematoda between winter and summer in the outer basin of Kongsfjorden, but higher individual biomass in spring. This was explained by the effect of the seasonal recruitment following the spring bloom.…”
Section: Seasonal Patterns In Size Structure Of Dominant Taxamentioning
confidence: 75%
“…However, environmental changes, such as rising temperatures coupled with enhanced food availability due to an increasing frequency of sea ice-free days per year, may have a stronger effect on succession than exposure time of disturbance. Wlodarska-Kowalczuk et al (2016) investigated relations between the marked seasonality in pelagic productivity and phytodetritus fluxes to the sea bottom on taxonomic composition and standing stocks of benthic communities. They detected no consistent differences in meio-and macrofaunal density, diversity or composition during the year, although possible responses to spring food supply in meiofaunal reproduction were observed in Nematoda, Harpacticoida and macrobenthic Crustacea.…”
Section: Partmentioning
confidence: 99%
“…Nematode and macrofaunal samples have been seen to have congruent patterns of assemblage structure in Araçá Bay, Brazil 11 . The environmental gradients associated with glacial meltwater in a fjord were associated with congruence of foraminifera and macrofauna 21 .…”
Section: Discussionmentioning
confidence: 98%